Label-free, sensitive colorimetric detection of mercury(II) by target-disturbed in situ seeding growth of gold triangular nanoprisms. (13th March 2020) - Ling, Rui; Zhang, Qianqian; Ren, Hang; Tursen, Janar; Bi, Junmin; Wu, Zhenglong; Qin, Weidong; Zhang, Chenling
Abstract: Gold nanomaterials have been used extensively in colorimetric detection of mercuric ions (Hg 2+ ) due to their shape- and size-dependent, ultrastrong localized surface plasmon resonance (LSPR). Conventional detection was performed by first synthesizing the nanomaterials, and then applying them to signal-transducing reactions. We herein report a convenient method for detecting Hg 2+ based on gold triangular nanoprisms (AuTNPs). During the seeding-growth process, Hg 2+ added to the growth solution was co-reduced and deposited on the high-energy facets of the gold seeds, affecting the deposition patterns of the subsequently generated Au 0 and ultimately leading to the formation of defective AuTNPs. Morphological changes were reflected by the in-plane dipole LSPR wavelength shift, which was proportionally related to the concentration of Hg 2+ . To improve the selectivity, the interference from Ag + was eliminated by a stepwise preparation-selective precipitation approach. Under the optimized conditions, Hg 2+ could be selectively detected with 20 min, with a detection limit of 0.12 nM. Finally, the method was successfully applied to detecting trace Hg 2+ in fortified drinking, mineral and rain water samples, with recoveries ranging from 95.17% to 110.6%.